Exploring Students' Engagement in Comprehending Analytical Exposition Texts through Gallery Walk Technique - Zulfa Tutuarima; Mochammad Hatip; Anita Fatimatul Laeli (Prominent, 2026)
This study aims to explore students' engagement in comprehending Analytical Exposition texts through the use of the Gallery Walk technique. Conducted in an eleventh-grade English class at a state senior high school in Jember during the 2024/2025 academic year, this research employed a qualitative descriptive method through observation, interviews, and documentation. The purpose was to investigate how the Gallery Walk technique influences students' behavioral, cognitive, and affective engagement during reading activities. The results showed that the Gallery Walk technique effectively enhanced students' behavioral, cognitive, and especially affective engagement. Students participated actively, demonstrated improved understanding, and showed enthusiasm during learning. The findings suggest that the Gallery Walk fosters a more interactive and motivating classroom environment, making it a beneficial strategy to improve reading comprehension and student engagement in English language learning.